EVALUASI KEBIJAKAN PENSIUN DINI PLTU BATUBARA DALAM KONTEKS TRANSISI ENERGI: IMPLIKASI TERHADAP KETAHANAN ENERGI DAN PEMBANGUNAN SOSIAL-EKONOMI INDONESIA - Bisri, M. Mustofah; Maharani, Safira Ika; Billa, Aurell Sava Fil Salsha (Universitas Islam Indonesia, 2024)
The early retirement policy for Coal-Fired Power Plants (PLTU) is a strategic step in Indonesia's energy transition towards a more sustainable future. This policy aims to reduce dependency on fossil fuels by accelerating the shift to renewable energy and reducing carbon emissions. However, this policy presents significant challenges to national energy security and its implications on socio-economic development, particularly in regions heavily reliant on coal-fired power plants. This study aims to evaluate the early retirement policy for PLTU in the context of energy transition and analyze its implications on energy security and socio-economic development in Indonesia. The method used is a qualitative approach with descriptive analysis based on data from official sources and related literature. The findings show that while this policy can accelerate the transition to cleaner energy, its implementation requires careful planning, strengthening renewable energy infrastructure, and addressing socio-economic impacts on coal sector workers. Furthermore, the policy needs to be supported by clear regulations and inclusive social policies to ensure a fair and sustainable energy transition. The study concludes that the early retirement policy for PLTU can contribute to sustainable energy development, as long as it is accompanied by mitigation measures that consider energy security and socio-economic well-being.